(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
The article discusses the methodological features of organizing the educational process of a physics course in higher education institutions in the field of construction. Specific examples of the effective organization of lectures and practical classes in the training of civil engineers in physics are given. There are recommendations and suggestions on the need to pay more attention to demonstration experience in organizing lesson processes. Thanks to this, the features of student career guidance, interdisciplinary integration and specialization in the field of construction were studied.